(untitled) (BIRDEM Medical Journal, 2020)
Twin-to-twin transfusion syndrome (TTTS) is an obstetric condition with high perinatal mortality, which develops when blood flows disproportionately from one fetus to another in a monochorionic twin pregnancy. Approximately 1 in 7 monochorionic pregnancies are affected with TTTS. The donor twin develops oligohydramnios and poor fetal growth, while the recipient twin develops polyhydramnios, heart failure and hydrops. Here we report two cases of severe TTTS in BIRDEM General Hospital 2 within a period of two years. It has been observed in different studies that, the mortality rate of both twins can be as high as 80% in TTTS depending on the stage of diagnosis and progression of the condition if untreated. In both our cases, the outcome was poor due to delayed diagnosis and lack of intrauterine therapies. So, there is an urgent need for timely diagnosis and appropriate management of this rare but complex condition which prompted us to report these two cases. Birdem Med J 2020; 10(3): 207-211